Emigration and democracy - Frédéric Docquier; Elisabetta Lodigiani; Maurice Schiff (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
Migration is an important and yet neglected determinant of institutions.This paper investigates the effect of emigration on the quality of home-country institutions. Using consider cross-sectional as well as dynamic-panel regressions for a large sample of developing countries, we find that openness to emigration (as measured by the general emigration rate) has a positive effect on the quality of institutions (as measured by standard democracy and economic freedom indices) in the migrants' home countries. The results are robust to a wide range of specifications and estimation methods.
Keywords: O1; F22; 330